(untitled) (Journal of Environmental Science and Natural Resources, 2016)
An investigation was conducted to assess the approximate nutrient composition of Miniket rice collected from different regions and market places of Tangail district in Bangladesh to understand actual fact. Moreover, mostly available variety BRRI-28 milled rice was also analysed to compare with the Miniket milled rice.Moisture, protein, fat, crude fibre, and ash content were higher in Miniket brown rice as compared to the parboiled milled rice except available carbohydrate. Among Miniket parboiled milled rice, Miniket TM-1 (Tangail Market-1) rice and Miniket TM-2 (Tangail Market-2) rice, the content of protein (7.04%), fat (0.37%), crude fibre (0.26%) and ash (0.58%) were comparatively higher in parboiled milled rice than that of two market samples. In a comparison among other cheaper coarse varieties like BRRI-28 and Miniket TM-1 rice and Miniket TM-2 rice, protein, fat, crude fibre and ash content were found lower in Miniket rice of TM-1 and TM-2 than BRRI-28. Beside chemical composition, some physical properties were studied including length, width, L/W ratio, shape and weight. J. Environ. Sci. & Natural Resources, 8(2): 97-102 2015